Crude Oil, Gold, Forex Rate and Indian Equity Market Interdependencies - Kumar, Dr. Pardeep; Singh, Dr. Satinderpal; Saxena, Dr. Charu (The journal of contemporary issues in business and government, 2021)
In the modern era of Friedman’s Flat World, investments are neither confined to a single economy nor to one type of investment. These days’ global investors seek investment across the different countries and explore the diverse markets, including equity, commodities, currency, and oil markets around the globe. Interdependencies among these key markets play a vital role in the success or ultimate failure of any such markets. This current research paper focuses on demonstrating the interlinkages between Crude and Gold rates, forex-rates and equity prices of the emerging Indian economy from 1993 to 2019 by deploying the cointegration tests given by Johansen and tests of unrestricted univariate Vector Autoregressive Model (VAR). The results failed to establish any kind of cointegration amongst the selected macroeconomic variables. Further, the results positively confirm the significant influence of the gold and equity prices on the crude-oil rates; the noticeable significant influence of crude and forex on the gold-prices; and marked the effect of forex-rates and equity-prices on each-other.